Primary Motor Cortex Excitability in Karate Athletes: A Transcranial Magnetic Stimulation Study - Vincenzo Monda (Frontiers in Physiology, 2017)
Purpose: The mechanisms involved in the coordination of muscle activity are not completely known: to investigate adaptive changes in human motor cortex Transcranial magnetic stimulation (TMS) was often used. The sport models are frequently used to study how the training may affect the corticospinal system excitability: Karate represents a valuable sport model for this kind of investigations for its high levels of coordination required to athletes. This study was aimed at examining possible changes in the resting motor threshold (rMT) and in the corticospinal response in karate athletes, and at determining whether athletes are characterized by a specific value of rMT.Methods: We recruited 25 right-handed young karate athletes and 25 matched non-athletes. TMS was applied to primary motor cortex (M1). Motor evoked potential (MEP) were recorded by two electrodes placed above the first dorsal interosseous (FDI) muscle. We considered MEP latencies and amplitudes at rMT, 110% of rMT, and 120% of rMT.Results: The two groups were similar for age (p > 0.05), height (p > 0.05) and body mass (p > 0.05). The TMS had a 70-mm figure-of-eight coil and a maximum output of 2.2 T, placed over the left motor cortex. During the stimulation, a mechanical arm kept the coil tangential to the scalp, with the handle at 45° respect to the midline. The SofTaxic navigator system (E.M.S. Italy, www.emsmedical.net) was used in order to correctly identifying and repeating the stimulation for every subject. Compared to non-athletes, athletes showed a lower resting motor threshold (p < 0.001). Furthermore, athletes had a lower MEP latency (p < 0.001) and a higher MEP amplitude (p < 0.001) compared to non-athletes. Moreover, a ROC curve for rMT was found significant (area: 0.907; sensitivity 84%, specificity 76%).Conclusions: As the main finding, the present study showed significant differences in cortical excitability between athletes and non-athletes. The training can improve cortical excitability inducing athletes' modifications, as demonstrated in rMT and MEP values. These finding support the hypothesis that the sport practice determines specific brain organizations in relationship with the sport challenges.